A new high‐quality set of singly (2H) and doubly (2H and 18O) stable isotope labeled reference waters for biomedical and other isotope‐labeled research. (9th January 2015) - Faghihi, V.; Verstappen‐Dumoulin, B. M. A. A.; Jansen, H. G.; van Dijk, G.; Aerts‐Bijma, A. T.; Kerstel, E. R. T.; Gröning, M.; Meijer, H. A. J.
Abstract : RATIONALE: Research using water with enriched levels of the rare stable isotopes of hydrogen and/or oxygen requires well‐characterized enriched reference waters. The International Atomic Energy Agency (IAEA) did have such reference waters available, but these are now exhausted. New reference waters thus had to be produced in sufficient quantity, and higher characterization quality was desired. METHODS: The reference waters have been prepared gravimetrically from three parent waters: natural water, pure 2 H water and highly 18 O‐enriched water. These parent waters have been thoroughly assessed for their full isotopic compositions. To ensure the integrity and correctness of the gravimetric procedure, validation measurements have been carried out on the isotopic composition of the produced reference waters by two of our laboratories. These measurements corroborate the values obtained on the basis of gravimetric data. RESULTS: Two new sets of three reference waters enriched in the stable isotopes have been produced and certified: one set of singly labeled waters, only enriched in 2 H, and another set of Doubly Labeled Waters, enriched in both 2 H and 18 O. They cover δ 2 H and δ 18 O values in the range of 800–16000 ‰ and 100–2000 ‰, respectively. The process has led to highly accurate isotopic values for these waters. CONCLUSIONS: These reference waters are now available (called IAEA‐604 to IAEA‐609). They will be valuable as reference materials for all fields using isotope labeling of water, most prominently, but not exclusively, biomedical research (body composition analyses, metabolic rate measurements). The two waters with the lowest enrichments will also be useful as anchor values for isotope measurements around the natural range. © 2015 The Authors. Rapid Communications in Mass Spectrometry published by John Wiley & Sons Ltd.